The 3Rs of Cell Therapy. (January 2017) - Caplan, Arnold I.; Mason, Chris; Reeve, Brock
Abstract: The 3Rs for a good education are "reading, 'riting, and 'rithmetic." The basis for good health care solutions for the emergent field of cell therapy in the future will also involve 3Rs: regulation, reimbursement, and realization of value. The business models in this new field of cell therapy will involve these 3Rs. This article brings forth realities facing this new industry for its approaches to provide curative health care solutions. Stem Cells Translational Medicine 2017;6:17–21